BIAYA PENGANGKUTAN SAMPAH DENGAN DUMPTRUK (STUDI KASUS KOTA MALANG) - Burhamtoro, Burhamtoro; Wicaksono, Achmad; Bisri, M.; Soemarno, Soemarno (FSTPT Indonesia, 2015)
The increasing volume of municipal solid waste resulting in the frequency and transportation costs on the temporary disposal station is increasing. This recent study is to examine the cost model based on the speed of the vehicle transporting waste using Dump Truck types from TPS to TPA with various brands of vehicles. This study applies survey method in which the researchers investigated the distance, time and volume of the waste transported by the entire fleet. The results of Model Municipal Solid Waste Transportation Costs obtained equation: Y = 7,66x2 – 580,81x + 15454,79 in whichY variable indicates the transportation cost (Rupiah/m3) and X variable shows the speed (km/ h). Cost of transporting waste to urban areas at optimum speeds obtain 37.91 Km/hour with minimum waste transportation costs Rp 4.445, -/m3.